Menopause, wellbeing and health: A care pathway from the European Menopause and Andropause Society. (September 2022) - Lambrinoudaki, Irene; Armeni, Eleni; Goulis, Dimitrios; Bretz, Silvia; Ceausu, Iuliana; Durmusoglu, Fatih; Erkkola, Risto; Fistonic, Ivan; Gambacciani, Marco; Geukes, Marije; Hamoda, Haitham; Hartley, Caiomhe; et al.
Highlights: Life expectancy has considerably increased since the last century and thus the menopause can now be considered a midlife event. Women's health is increasingly recognized as a global health priority and the complications of estrogen deficiency and ageing present an enormous problem to healthcare systems. This clinical guide provides a practical stepwise approach for all health professionals dealing with menopausal and postmenopausal health. Treatment options should be individualized and range from menopausal hormone therapy to non-hormonal alternatives and lifestyle modifications. Abstract: This care pathway from the European Menopause and Andropause Society (EMAS) provides an updated pathway for monitoring and guidance of women at midlife, focusing on those approaching the end of the reproductive life-cycle, going through the menopausal transition and beyond. The care pathway is written by professionals involved in women's health and provides a stepwise individualized approach, stratified according to needs, symptoms and reproductive stage. Furthermore, the pathway provides details on screening for chronic diseases related to menopause and ageing. Treatment options for climacteric symptoms range from menopausal hormone therapy to non-hormonal alternatives and lifestyle modifications. Therapy should be tailored to personal needs and wishes. The pathway aims to offer a holistic, balanced approach for monitoring middle-aged women, aiming to control health problems effectively and ensure healthy ageing.